Implikasi Legasi Pendidikan dalam Matius 28:18-20 bagi Gereja Masa Kini - Yakub Hendrawan Perangin Angin; Yonatan Alex Arifianto; Tri Astuti Yeniretnowati (DIDAKTIKOS: Jurnal Pendidikan Agama Kristen Duta Harapan, 2021)
Discipleship can be said to have been known for a very long time in the Christian community, but in practice today not many people have professed to believe in Jesus Christ as Savior and His Lord is involved in the discipleship process even to have the desire to make disciples of other believers. This is the problem facing the church as a believer in Christ today. The writing of this journal is intended to direct the perspective of believers who are called Christians because they believe in what has been taught and imitated by Jesus Christ by reviewing the Great Commission which was bequeathed by the Lord Jesus to His disciples. The method in writing this journal is a qualitative method with a library approach. The conclusion of this writing is the importance of remembering the legacy of the Great Commission that Christ has taught and modeled and how all Christians are called to pass it down continuously to the next generations of believers. AbstrakPemuridan dapat dikatakan sudah sangat lama dikenal dalam komunitas Kristen, namun pada praktiknya saat ini tidak banyak orang yang sudah mengaku percaya kepada Yesus Kristus sebagai juruselamat dan Tuhan-nya terlibat dalam proses pemuridan bahkan untuk memiliki kerinduan memuridkan orang percaya lainnya pun tidak. Inilah persoalan yang dihadapi gereja sebagai orang percaya kepada Kristus saat ini. Penulisan jurnal ini ditujukan untuk mengarahkan perspektif orang percaya yang disebut orang Kristen karena percaya kepada apa yang sudah diajarkan dan diteladankan oleh Yesus Kristus dengan mengupas kembali Amanat Agung yang diwariskan Tuhan Yesus kepada para murid-Nya. Metode dalam penulisan jurnal ini adalah metode kualitatif dengan pendekatan kepustakaan. Kesimpulan dari hasil penulisan ini adalah pentingnya mengingat kembali warisan Amanat Agung yang sudah Kristus ajaarkan dan teladankan dan bagaimana semua orang Kristen terpanggil untuk mewariskannya kembali terus menerus ke generasi-generasi orang percaya selanjutnya.